2013
DOI: 10.3892/ol.2013.1231
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of vascular endothelial growth factor are increased and correlate with malnutrition, immunosuppression involving MDSCs and systemic inflammation in patients with cancer of the digestive system

Abstract: Vascular endothelial growth factor (VEGF) reportedly has an important role in the progression of malignant neoplasms and has been reported to induce myeloid-derived suppressor cells (MDSCs) that appear in cancer and inflammation. In the present study, serum concentrations of VEGF were measured in patients with digestive system cancer and the correlations with nutritional damage, immune suppression and systemic inflammation were analyzed. A significant increase in VEGF serum levels was observed in patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 19 publications
0
44
2
2
Order By: Relevance
“…Immune suppression was closely associated with increased NLR as the levels of SI were significantly inversely correlated to increased NLR. The authors previously reported that increasing levels of circulating myeloid-derived suppressor cells (MDSCs) correlate with decreased SI, malnutrition, and increased vascular endothelial growth factor (VEGF) levels in patients with cancer (36,37). The authors speculated that immune suppression may also occur with increased MDSC levels, activated by inflammation or tumor-produced VEGF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immune suppression was closely associated with increased NLR as the levels of SI were significantly inversely correlated to increased NLR. The authors previously reported that increasing levels of circulating myeloid-derived suppressor cells (MDSCs) correlate with decreased SI, malnutrition, and increased vascular endothelial growth factor (VEGF) levels in patients with cancer (36,37). The authors speculated that immune suppression may also occur with increased MDSC levels, activated by inflammation or tumor-produced VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…The authors previously reported that malnutrition or hypoalbuminemia correlates well with immune suppression, systemic inflammation and suppression of cell-mediated immunity (34)(35)(36)(37)(38). Systemic inflammation may underlie these conditions, which are prominent in patients with advanced cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Although a causal relationship between inflammation and the innate immunity in cancerbearing hosts is widely accepted today, the precise cellular mechanisms mediating this relationship have not been elucidated. We have reported several immunological factors, including myeloid-derived suppressor cells (MDSCs), interleukin (IL)-17, and vascular endothelial growth factor (VEGF), in various types of cancer [2][3][4] . IL-17 is a proinflammatory cytokine that is primarily secreted by T helper (Th)17 cells and innate lymphoid cells including γδT cells and natural killer cells 5,6) .…”
Section: Introductionmentioning
confidence: 99%
“…Vascular endothelial growth factor (VEGF) is an angiogenic factor that has been characterized extensively and is expressed at high levels in the majority of tumors. In the local tumor environment, the protein modulates blood vessel growth, vascular permeability and vascular remodeling, while VEGF produced by tumors also accumulates in the circulation and induces CASS (2,8).…”
Section: Introductionmentioning
confidence: 99%
“…Cancer-associated systemic syndrome (CASS) refers to the cluster of symptoms that typically includes fever, anemia, endocrine and neurological disorders, gastrointestinal dysfunction, adipose and muscle atrophy, hepatic peliosis, ascites and kidney failure (1,2). The syndrome can also manifest as cachexia and paraneoplastic syndrome in severe cases (1,3).…”
Section: Introductionmentioning
confidence: 99%